Flash flood impact in Kuala Lumpur – approach review and way forward - Norashikin Samsuri,; Rabieahtul Abu Bakar,; Tanot Unjah, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
The understanding of the impact of flash floods is carried out by identifying the main causes of flooding. Measures have been undertaken to reduce the impact of flooding however, several recommendations are identified to address the problem more effectively. This paper is based on the analysis of the factors that has contributed to the occurrence of flash floods in urban areas particularly Malaysia’s capital, Kuala Lumpur. Rapid development occurs here, leads to the compromise of green and forested areas that serve as the absorption of water run-off, causing drainage associated problem, moreover, when not managed effectively and obsolete drainage design that requires costly maintenance. Steps taken to reduce this problem are mainly structured approach which involves the construction of smart tunnel to diverted large quantities of water from the road surface to existing natural pond, widening and deepening of the drainage system, building reservoirs and dams for storm water at the upstream area. Meanwhile, the non-structured approached currently involves cleaning of the main waterway of Sungai Klang and Sungai Gombak of debris. Recommendation for future works is more active non structured approach that have been prove to be cost effective with greater impact to the livelihood of the people.